DYNASTIES : LIONS - Moss, Stephen, 1960-; Trewin, Anna; Pitts, Sorrel (London : PENGUIN BOOKS, 2020)
Penguin Readers is a graded reading series for English Language Teaching (ELT) markets, designed for teenagers and young adults learning English as a foreign or second language.
Sometimes families are happy, and sometimes they fight. Sometimes life is good, and sometimes it is not easy. It is the same for the Marsh Lions in Kenya's Masai Mara, and for all animal families.
Includes questions and excercises
Keywords: Readers -- Lions; Lions